Pengaruh Debt To Equity Ratio, Return On Asset, Current Ratio Terhadap Dividend Payout Ratio Pada Perusahaan Sub Sektor Farmasi - Melinda Ibrahim (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2019)
The profit acquisition of go-public pharmaceutical subsector companies in Indonesia Stock Exchange has been fluctuating since 2014 through 2017.  Even, there have been two companies indicating a negative trend, namely Indofarma, Inc. and Merck Sharp Dohme Pharma, Inc.  This circumtance has certainly affected on the earning per share in the companies.  The study aimed to find out and analyze the significance of the effect of the Debt to Equity Ratio, Return On Asset, and Current Ratio on the Dividend Payout Ratio at Go-Public Pharmaceutical Subsector Companies in Indonesia Stock Exchange, partially and simultaneously.  This study used a qualitative method through ratio analysis.  The techniques of analysis applied were by using the classical assumption test and multiple regressions.  The sample covered 8 go-public pharmaceutical subsector companies in Indonesia Stock Exchange during 2014 through 2017.  The results indicated that the Debt to Equity Ratio (DER), Return On Asset (ROA), and Current Ratio (CR) simultaneously had a positive and significant effect on the Dividend Payout Ratio (DPR), and only Return On Asset (ROA) partially had a significant effect on the Dividend Payout Ratio (DPR).